Remote Delivery of Service: A Survey of Occupational Therapists' Perceptions. (September 2022) - Almog, Tehila; Gilboa, Yafit
Background: Telehealth has been declared an accepted method of occupational therapy (OT) service delivery and has been shown to be effective. However, studies done before the outbreak of coronavirus disease (COVID-19) show that most occupational therapists didn't use it. Aim: The aim of this exploratory study was to examine the perceptions of occupational therapists regarding remote delivery of service following the COVID-19 outbreak. Material and methods: An online survey, including 11-item five-point Likert scale, and 2 open-ended questions were distributed to occupational therapists. Results: Responses were received from 245 Israeli occupational therapists. The majority of the participants (60%) strongly agreed that remote delivery allows an ecological and effective intervention, while 76% strongly agreed that an ideal treatment is one that would combine telehealth with in-person intervention. Qualitative findings indicated that the most significant advantage was providing care in the natural environment and improving accessibility to the service. The most salient barriers were limitations of the therapeutic relationship and threats on clinical reasoning. Conclusion: The study results highlight the complexity of telehealth. Findings indicate that overall occupational therapists perceive remote care as an effective and legitimate service delivery method that cannot be used as an alternative to in-person treatment. These findings can help in developing intervention programs for remote treatment, and their implementation.